All‐diamond optical assemblies for a beam‐multiplexing X‐ray monochromator at the Linac Coherent Light Source. (1st August 2014) - Stoupin, S.; Terentyev, S. A.; Blank, V. D.; Shvyd'ko, Yu. V.; Goetze, K.; Assoufid, L.; Polyakov, S. N.; Kuznetsov, M. S.; Kornilov, N. V.; Katsoudas, J.; Alonso‐Mori, R.; Chollet, M.; et al.
Abstract : A double‐crystal diamond (111) monochromator recently implemented at the Linac Coherent Light Source (LCLS) enables splitting of the primary X‐ray beam into a pink (transmitted) and a monochromatic (reflected) branch. The first monochromator crystal, with a thickness of ∼100 µm, provides sufficient X‐ray transmittance to enable simultaneous operation of two beamlines. This article reports the design, fabrication and X‐ray characterization of the first and second (300 µm‐thick) crystals utilized in the monochromator and the optical assemblies holding these crystals. Each crystal plate has a region of about 5 × 2 mm with low defect concentration, sufficient for use in X‐ray optics at the LCLS. The optical assemblies holding the crystals were designed to provide mounting on a rigid substrate and to minimize mounting‐induced crystal strain. The induced strain was evaluated using double‐crystal X‐ray topography and was found to be small over the 5 × 2 mm working regions of the crystals.